Effect of renin–angiotensin system inhibitors in patients with cancer treated with anti-VEGF therapy. Issue 2 (8th December 2022) - Moriyama, Shohei; Hieda, Michinari; Kisanuki, Megumi; Kawano, Shotaro; Yokoyama, Taku; Fukata, Mitsuhiro; Kusaba, Hitoshi; Maruyama, Toru; Baba, Eishi; Akashi, Koichi; Fukuda, Haruhisa
Abstract : Background: Cancer treatment with vascular endothelial growth factor signalling pathway (VSP) inhibitors frequently causes hypertension. Although previous reports suggested that the antihypertensive drug renin–angiotensin system inhibitor (RASI) may have a positive synergistic effect with VSP inhibitors, the actual impact on clinical outcomes is unknown. Objectives: The study aims to clarify whether RASIs exhibit clinical benefits for patients with cancer with hypertension. Method: From the Longevity Improvement and Fair Evidence Study database, comprising Japanese claims data between 2016 and 2020, we reviewed 2380 patients treated with VSP inhibitors who received antihypertensive treatment during cancer therapy. The patients were classified into two groups: with-RASI (n=883) and without-RASI (n=1497). In addition, 1803 of these patients treated for hypertension with RASI-only (n=707) or calcium channel blocker-only (n=1096) were also reviewed. The time-to-treatment failure (TTF), the interval from initiation of chemotherapy to its discontinuation, was applied as the primary endpoint. Results: The median TTFs were 167 (60–382) days in the with-RASI group and 161 (63–377) days in the without-RASI group (p=0.587). All models, including Cox proportional hazard models and multiple propensity score models, did not reveal the superiority of with-RASI treatment. In the propensity score matching model, the HR for treatment with-RASI compared with that for without-RASI was 0.96 (95% CI 0.86 to 1.06, p=0.386). In addition, the TTFs of RASI-only were not superior to calcium channel blocker-only (p=0.584). Conclusions: RASIs for hypertension do not benefit clinical outcomes during cancer therapy with VSP inhibitors. In addition, RASIs and calcium channel blockers have comparable clinical efficacy as first-line antihypertensive.